Cognitive Function in Survivors of Out-of-Hospital Cardiac Arrest After Target Temperature Management at 33°C Versus 36°C. Issue 15 (14th April 2015) - Lilja, Gisela; Nielsen, Niklas; Friberg, Hans; Horn, Janneke; Kjaergaard, Jesper; Nilsson, Fredrik; Pellis, Tommaso; Wetterslev, Jørn; Wise, Matt. P.; Bosch, Frank; Bro-Jeppesen, John; Brunetti, Iole; et al.
<x xml:space="preserve">Abstract</x> Background— Target temperature management is recommended as a neuroprotective strategy after out-of-hospital cardiac arrest. Potential effects of different target temperatures on cognitive impairment commonly described in survivors have not been investigated sufficiently. The primary aim of this study was to evaluate whether a target temperature of 33°C compared with 36°C was favorable for cognitive function; the secondary aim was to describe cognitive impairment in cardiac arrest survivors in general. Methods and Results— Study sites included 652 cardiac arrest survivors originally randomized and stratified for site to temperature control at 33°C or 36°C within the Target Temperature Management trial. Survival until 180 days after the arrest was 52% (33°C, n=178/328; 36°C, n=164/324). Survivors were invited to a face-to-face follow-up, and 287 cardiac arrest survivors (33°C, n=148/36°C, n=139) were assessed with tests for memory (Rivermead Behavioural Memory Test), executive functions (Frontal Assessment Battery), and attention/mental speed (Symbol Digit Modalities Test). A control group of 119 matched patients hospitalized for acute ST-segment–elevation myocardial infarction without cardiac arrest performed the same assessments. Half of the cardiac arrest survivors had cognitive impairment, which was mostly mild. Cognitive outcome did not differ (P>0.30) between the 2 temperature groups (33°C/36°C). Compared with control subjects with ST-segment–elevation myocardial infarction, attention/mental speed was more affected among cardiac arrest patients, but results for memory and executive functioning were similar. Conclusions— Cognitive function was comparable in survivors of out-of-hospital cardiac arrest when a temperature of 33°C and 36°C was targeted. Cognitive impairment detected in cardiac arrest survivors was also common in matched control subjects with ST-segment–elevation myocardial infarction not having had a cardiac arrest. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01946932.